Analisis Kualitas Naskah Ujian Akhir Semester Mata Kuliah Bahasa Inggris II Politeknik Negeri Lampung Tahun 2006 - Refdi Akmal (Politeknik Negeri Lampung, 2008)
It is believed that without the evaluation it would be almost impossible to teach. As students need to know their abilities, teachers use some kind of evaluations. Evaluation of teaching learning process can be administrated in the form of tests. In other words teaching must be followed by testing. The information gained can be useful for both students and teacher. Hence there are two points interrelated. Firstly, the test is concerned with the teaching that has taken place. It is that the test administered should give the students feeling that the teacherâ€™s evaluation matches what they have taught and sense of accomplishment. Secondly, the teaching is concerned with the test. The teacher can diagnose his effort in his teaching whether or not his teaching has been effective. Madsen (1987) pointed out that the criteria of a good test comprise: (1) validity, (2) reliability, (3) difficulty level, and (4) discrimination power. This research was to know and describe quality of semester II English test for the students of The State Polytechnic of Lampung (Polinela) in the year 2006. The study showed that the Semester II English Test administered for the students did not meet the expected level of validity, reliability, level of difficulty nor discrimination power of a good test.Â Key words: evaluation, validity, reliability, difficulty level, discrimination power.